Oxidation of natural targets by dioxiranes. Part 6: on the direct regio- and site-selective oxyfunctionalization of estrone and of 5α-androstane steroid derivatives - D’Accolti, Lucia; Fusco, Caterina; Lampignano, Giuditta; Capitelli, Francesco; Curci, Ruggero (Tetrahedron letters, 2008)
Methyl(trifluoromethyl)dioxirane ( 1b) was employed to achieve under mild conditions the regio- and site selective direct synthesis of new oxyfunctionalized steroids 7 and 8. Using methyl(trifluoromethyl)dioxirane ( 1b), 3β,6α,17β-triacetoxy-5α-androstane ( 6) could be selectively transformed into its C-14 hydroxy derivative ( 7) and into the valuable C-12 ketone steroid ( 8), in high yields under mild reaction conditions. Similarly, the oxidation of 3α-estrone acetate ( 4) with 1b was carried out to yield selectively the steroid C-9 hydroxy derivative ( 5). The high regio- and site-selectivity attained demonstrates that the powerful dioxirane 1b is the reagent of choice to synthesize valuable oxyfunctionalized steroid derivatives.